Analysing the restrictions on freedom of speech in Malaysia / Azif Hakiemi Abdullah, Muhammad Hariz Abd Mutalib and Mohamad Husaini Shaharuddin - Abdullah, Azif Hakiemi; Abd Mutalib, Muhammad Hariz; Shaharuddin, Mohamad Husaini (Faculty of Law, 2014)
This work involves the critiques and also to analyze the principle of law of freedom of speech and the restrictions imposed on this right. In Malaysia, the law which governs the fundamental right of freedom of speech is by the virtue of Article 10 of the Federal Constitution of Malaysia. This right shall include freedom to hold opinions and to receive and impart information and ideas without interference by the public authorities’ regardless frontiers. In simpler words, this right also includes the right to express one's ideas and opinions freely through speech, writing, and other forms of communication but without deliberately causing harm to others' character or reputation by false or misleading statements. Freedom of press is also a part of freedom of expression. However, to balance with the national security issues, Parliament has entrenched some restrictions on this particular liberty by introducing various laws which limit this right to certain extent. Therefore, this study will focus into the relevancy and rationale of those restrictions so that it could be improve for the benefit of the nation.